2011
DOI: 10.1080/00288233.2011.607831
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soil pH on NOxand N2O emissions from bovine urine applied to soil columns

Abstract: The nitrous oxide (N 2 O) molecule is both a greenhouse gas and a precursor to the formation of nitric oxide (NO) in the stratosphere, which is subsequently involved in catalytic destruction of ozone (O 3 ). Tropospheric NO can form NO 2 with both gases (NO x ) able to react with volatile organic compounds to produce the detrimental O 3 molecule. Information on how NO and N 2 O emissions respond to agricultural management is lacking. Limited data suggest N 2 O emissions following bovine urine deposition may va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 43 publications
2
12
0
1
Order By: Relevance
“…Khan et al . () measured N 2 O emissions induced by bovine urine 2 weeks after manipulating the pH by liming, and found that the accumulated emissions increased with liming. Goodroad et al .…”
Section: Discussionmentioning
confidence: 99%
“…Khan et al . () measured N 2 O emissions induced by bovine urine 2 weeks after manipulating the pH by liming, and found that the accumulated emissions increased with liming. Goodroad et al .…”
Section: Discussionmentioning
confidence: 99%
“…Soil chemical and physical characteristics were previously reported by Khan et al (2011). In brief, the soil had a pH of 6.0, bulk density of 0.95 g/cm 3 , and total C and N contents of 2.9 and 0.26 mg/kg, respectively.…”
Section: Experimental Site and Treatmentsmentioning
confidence: 99%
“…Thus factors affecting these processes, such as soil pH and moisture content, also affect NO x emissions (Davidson 1992;Khan et al 2011). Since NO is an obligate intermediary in denitrification there is less opportunity for the emission of NO when soil water-filled pore space (WFPS) becomes elevated because complete denitrification is favoured as a result of the lower relative gas diffusivities .…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, the effect of pH on N 2 O emission is complex. Soil pH is an important factor affecting both nitrification and denitrification [38]. Low pH may affect both the nitrification and denitrification processes and inhibit the activity of the N 2 O reductases responsible for the conversation of N 2 O during denitrification, which then leads to increased N 2 O emissions [39].…”
Section: Influence Factors Of Ghg Emissionmentioning
confidence: 99%